ANALISIS INFORMASI CITRA MRI GENU POTONGAN AXIAL ANTARA SEQUENCE SHORT TAU INVERSION RECOVERY (STIR) DAN SEQUENCE T2-SPECTRAL ATTENUATION INVERSION RECOVERY (T2-SPAIR) - Ramandasari, Suci; Gunawati, Shinta; Winarno, Guntur; Edy W, Mahfud; Heriyanto, Fransiscus (Perhimpunan Radiografer Indonesia (PARI), 2021)
Background : This research aims to analyze the information of genu axial section image quality using T2 STIR and SPAIR sequences at Mayapada Hospital. Methods : The design of this research is quantitative analytics with experimental approaches conducted at the Mayapada Hospital Radiology Installation with the study population taken from all MRI genu examination patients during September-December 2020 with a study sample of 5 patients aged 18-40 years with various complaints on Genu. Then, reconstruction is carried out with a stunt cut techniques on STIR and SPAIR sequence. Result : The result of this study showed a difference in T2 STIR d an T2 SPAIR with p value of 0.025 < 0.05. Conclusion : The contrast of MRI genu sequence STIR is brighter than SPAIR sequence as evidenced by the calculation of CNR value of STIR sequence 8,388 higher than SPAIR sequence value of 5,345. So it can be concluded that in MRI genu examination, the CNR value on the STIR sequence of a stunt pieces with SPAIR sequence of a stunt pieces has a significant difference.